The natural course of bicuspid aortic valve in athletes - Spataro, A.; Pelliccia, A.; Rizzo, M.; Biffi, A.; Masazza, G.; Pigozzi, F. (International Journal of Sports Medicine, 2008)
The purpose of this study was to evaluate the impact of a long-term athletic training on the clinical course of bicuspid aortic valve. A group of 81 athletes (73 M, 8 F, 22.7 ± 5.6 years) with bicuspid aortic valve was collected. Based on clinical and echocardiographic criteria, athletes were initially divided into 2 groups: the low-risk (51 athletes) and the high-risk group (30 athletes). The high-risk athletes were disqualified from training and competitions after the first evaluation. Over the follow-up period, all of them showed significant worsening of morphologic and hemodynamic features of bicuspid aortic valve; two underwent surgical valvular repair and one of them died suddenly. Over the same period, six of the initially low-risk athletes (7 %) showed significant worsening of morphologic features of bicuspid aortic valve and/or incidence of symptoms which led to their disqualification from competition. At the end of follow-up, we observed that in high-risk subjects the progression of valvular disease occurred independently from the former athletic activity and that the majority of athletes with mild bicuspid aortic valve had a benign clinical course. However, athletes with bicuspid aortic valve should be viewed with caution, and continued clinical surveillance would be mandatory.